THE INFLUENCE OF FRAUD STAR AND DIGITAL BANKING ON FFR IN BANKING SECTOR AND THE MODERATING ROLE OF FOREIGN OWNERSHIP - Erina Normasari; Sekar Mayangsari (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2022)
This study aims to analyze the influence of Fraud Star dimensions consisting of Pressure, Opportunity,Rationalization, Capability, Integrity, and Digital Banking in detecting the occurrence of Fraudulent FinancialReporting (FFR) with the moderating role of Foreign Ownership. This study uses 100 sample datas from bankingcompanies listed on the Indonesia Stock Exchange (IDX) which were selected using purposive sampling method.The analytical methodology used is panel regression analysis. The results of this study indicate that Pressure has apositive and significant effect on FFR. In addition, the moderating role of Foreign Ownership is able to strengthen the positive influence of Pressure on FFR. However partially, Opportunity, Rationalization, Capability, Integrity and Digital Banking have no effect on FFR. Foreign Ownership also cannot moderate the relationship of Opportunity,Rationalization, Capability, Integrity and Digital Banking to FFR. The results of statistical tests indicate that theFraud Star dimension is a unity that can effect the occurrence of FFR. Likewise with Integrity as the last dimension ofFraud Star which is adherence to moral values or code of ethics that must be adhered to and become important basis in the banking sector. This study implies that the occurrence of FFR can be influenced, prevented and minimized by observing the ROA value, the proportion of independent commissioners, auditor and director turnover, stock price performance (MBR), digitization, the proportion of foreign shares, liquidity risk and the size of banking companies simultaneously. In addition, banks are expected to strengthen the control function in line with the increase in performance targets and employee performance bonuses.